NICOTINE IN TRADITIONAL TOBACCO AND MODERN ELECTRONIC SMOKING DEVICES: THE NATURE OF DEPENDENCE FORMATION AND COGNITIVE FEATURES OF SMOKERS - Урядова, Галина Урядова; Русецкая, Наталья Юрьевна (Medicine in Kuzbass, 2024)
The problem of smoking is widespread among the young able-bodied population of Russia. Electronic nicotine delivery systems are in great demand among smokers as a «light» alternative to traditional tobacco products. The aim of the present investigation was to study is devoted to the study of the nature of addiction formation and cognitive characteristics of smokers of traditional and modern electronic smoking systems. Materials and methods. The participants of the experiment underwent psychodiagnostic testing to assess the concentration of attention and the volume of visual, auditory, motor-auditory and combined memory, as well as a questionnaire. Results. It was found that 46.4 % of those participating in the experiment have been smoking for more than two years, 14.3 % for more than 5 years. At the same time, 26.3 % of the participants in the experiment smoke 2-3 times a day, 21.1 % – 3-5 and 15.8 % – 5-10 times. The majority (71.4 %) of those surveyed consider electronic cigarettes less harmful than tobacco products. Most of the respondents smoke to relax and are sure that smoking helps to cope with psychological problems, hunger, maintains attention and efficiency. At the same time, 60 % of the participants tried to quit the addiction, but to no avail. The participants of the experiment are characterized by such types of smoking behavior as «relaxation» and «support», and the physical dependence on nicotine has not yet been expressed. At the same time, slightly more than a quarter of participants who smoke already suffer from chronic diseases. It has been established that the use of both tobacco cigarettes and electronic cigarettes negatively affects the cognitive functions of smokers, and it is the amount of memory, but concentrated active mindfulness does not depend on smoking. Conclusion. The results of the study indicate that the use of both traditional tobacco and electronic nicotine delivery systems negatively affects the memory capacity of smokers, but at the same time, more than seventy percent of the participants in the experiment considered electronic cigarettes to be less harmful than tobacco products. The identified negative cognitive manifestations of smoking are expected to increase with increasing smoking experience.